Family history of diabetes in both parents is strongly associated with impaired residual β‐cell function in Japanese type 2 diabetes patients. Issue 3 (13th December 2019) - Iwata, Minoru; Kamura, Yutaka; Honoki, Hisae; Kobayashi, Kaori; Ishiki, Manabu; Yagi, Kunimasa; Fukushima, Yasuo; Takano, Atsuko; Kato, Hiromi; Murakami, Shihou; Higuchi, Kiyohiro; Kobashi, Chikaaki; et al.
Abstract: Aims/Introduction: The objective of the present study was to clarify the association of the type and number of first‐degree family history of diabetes (FHD) with the clinical characteristics, especially with residual β‐cell function, in type 2 diabetes patients. Materials and Methods: A total of 1, 131 type 2 diabetes patients were recruited and divided into four groups according to FHD information as follows: (i) patients without FHD (FHD−); (ii) those with at least one sibling who had diabetes without parental diabetes (FHD+); (iii) those with one parent (FHD++); or (iv) those with both parents (FHD+++) who had diabetes with or without a sibling with diabetes. Results: The percentages of the FHD−, FHD+, FHD++ and FHD+++ groups were 49.4%, 13.4%, 34.0% and 3.2%, respectively. Patients in the FHD++ and FHD+++ groups were significantly younger at the time of diabetes diagnosis ( P < 0.001) than those in the FHD− and FHD+ groups, even after adjusting for confounding factors. In addition, the levels of insulin secretion were significantly lower in the patients in the FHD+, FHD++ and FHD+++ groups than those in the FHD− group ( P < 0.05) after adjusting for confounding factors, and the patients in the FHD+++ group presented with the lowest levels of insulin secretion among the four groups. Conclusions: Our results showed that in type 2 diabetes patients, the degree of the associations between FHD and clinical characteristics differs according to the number and the type of FHD. In particular, FHD in both parents is most strongly associated with impaired residual β‐cell function. Abstract : In type 2 diabetes patients patients, the degree of the associations between family history of diabetes and clinical characteristics differs according to the number and the type of family history of diabetes. In particular, family history of diabetes in both parents is most strongly associated with impaired residual β‐cell function.